Detoxification of certain toxins (triterpenoids) in neem (Azadiracta indica) seed-cake - KUMAR, O SUNEEL; REDDY, K JOJI; REEDY, G V N (The Indian Journal of Animal Sciences, 2014)
Neem seed-cake (NSC) is bitter and contains certain toxic principles (triterpenoids), which limit its usage as an animal feed. To detoxify these toxins different physical, chemical and combination of physical and chemical methods were applied. These triterpenoids were estimated quantitatively by analytical HPLC. Water washing removed 82.53% of azadirachtin, 53.13% of nimbin and 35.89% of salannin. The chemical treatments (4% urea with 40% moisture) removed 45.5% azadirachtin, 75.94% nimbin and 98.07% salannin. Water washing followed by urea treatment removed 83.27% azadirachtin and 100% nimbin and salannin.